Experimental Evidence and Clinical Implications of Pituitary Adenoma Stem Cells - Würth, Roberto; Thellung, Stefano; Corsaro, Alessandro; Barbieri, Federica; Florio, Tullio (Frontiers in Endocrinology, 2020)
Pituitary adenomas, accounting for 15% of diagnosed intracranial neoplasms, are usually benign and pharmacologically and surgically treatable; however, the critical location, mass effects and hormone hypersecretion sustain their significant morbidity. Approximately 35% of pituitary tumors show a less benign course since they are highly proliferative and invasive, poorly resectable and likely recurring. The latest WHO classification of pituitary tumors includes pituitary transcription factor assessment to determine adenohypophysis cell lineages and accurate designation of adenomas, nevertheless little is known about molecular and cellular pathways which contribute to pituitary tumorigenesis. In malignant tumors the identification of cancer stem cells radically changed the concepts of both tumorigenesis and pharmacological approaches. Cancer stem cells are defined as a subset of undifferentiated transformed cells from which the bulk of cancer cells populating a tumor mass is generated. These cells are able to self-renew, promoting tumor progression and recurrence of malignant tumors, also conferring cytotoxic drug resistance. On the other hand, the existence of stem cells within benign tumors is still debated. The presence of adult stem cells in human and murine pituitaries where sustain the high plasticity of hormone-producing cells, allowed the hypothesis that putative tumor stem cells might originate and can be identified in pituitary adenomas, reinforcing the concept that the cancer stem cell model could also be applied to pituitary tumorigenesis. In the last few years, the isolation and phenotypic characterization of putative pituitary adenoma stem-like cells was performed using a wide and heterogeneous variety of experimental models and techniques, although the role of these cells in adenoma initiation and progression is still not completely definite. The assessment of possible pituitary adenoma-initiating cell population would be of extreme relevance to better understand pituitary tumor biology and to identify novel potential diagnostic markers and pharmacological targets. In this review, we summarize the most updated studies focused on the definition of pituitary adenoma stem cell phenotype and their functional features, highlighting the biological processes and intracellular pathways potentially involved in driving tumor growth, relapse, and therapy resistance.